(untitled) (mathematica didactica, 2022)
Generally, questioning is perceived as an important learning strategy for university mathematics courses. However, the characteristics of questions in mathematical learning contexts are rather undefined. By means of questions from first term undergraduates, we constructed an analytical framework for describing mathematical questions. The article outlines the development of our analytical framework by using the methodology of grounded theory. Furthermore, the framework and its three categories‘content level of the question’, ‘teaching-learning context’ and ‘linguistic perspective’ are presented. Finally, an outlook is provided on how the framework may be used in further research and teaching.